Mycophenolate Mofetil-Related Enterocolitis and Weight Loss: A Pediatric Case Series. (23rd October 2012) - Dykes, Dana M. H.; Moore, Sean R.; Polk, D. Brent; Rosen, Michael J.; Wills, Marcia L.; Morris, Brian; Maclin, Jeanine S.; Nogueira, Janaina; Katz, Avi; Hunley, Tracey E.; Pugh, Judith; Saeed, Shehzad
Abstract : Mycophenolate mofetil (MMF) is an immunosuppressive medication utilized in the management of both autoimmune and solid organ transplant patients. Diarrhea is a common gastrointestinal side effect of MMF, but more severe forms of GI symptoms are described in renal transplant patients with a distinct pattern of histopathologic change, similar to graft-versus-host disease or Crohn's disease. This rare entity, commonly referred to as "MMF-related enterocolitis, " has been described in adult patients, mostly in renal transplant patients, and in only two pediatric renal transplant patients. In previously reported cases, symptoms and abnormal histopathology improve with dose reduction of MMF. We describe a series of three pediatric patients with varied underlying disease process who presented with severe diarrhea and histopathologic findings characteristic of MMF-related enterocolitis, who share a novel finding of weight loss as a complication of MMF-related enterocolitis in pediatric patients.